A reception history of the letter to the Hebrews in England, 1547-1685 - Padley, K (2016)
The interpretation of the letter to the Hebrews made a distinctive contribution to doctrinal construction, polemical controversy, and evolution of scripture-critical technique in the early modern period. This was because many of its themes and passages were considered significant to contemporary theological debates. Hebrews therefore offers an important case study for biblical reception history. This thesis adopts a diachronic approach, highlighting the priorities and worries of English Hebrews exegetes between the reigns of Edward VI and Charles II, and asks how these shifts catalysed hermeneutical advances towards higher biblical criticism. Calvin interpreted Hebrews’ theology of sacrifice as an antidote to Catholic christology, soteriology, and beliefs about the mass. His thinking was adopted by Elizabethan Protestant readers, popularised through public documents like the Reformation Bibles (chapter one), and analysed in detail by sermons and lectures (chapter two). The reception of Hebrews also illustrates established historiography about the break-down of Reformed hegemony in England. Chapter three demonstrates how the use of the epistle by anti-puritans clashed with the censored Reformed exegete William Jones. Scholars of the seventeenth century have largely ignored how Hebrews’ latent supersessionism promoted innovation in Church and society. Chapter four explores the way in which civil war Socinians expounded Christ’s priesthood in terms of heavenly expiation, while radicals seized on the epistle’s potential to support their vision of politico-religious liberation. Initially the Reformed countered by defending the trinity and Chalcedonian christology, as shown from mid-century exegesis in chapter five. However, two writers realised the underlying challenge of supersessionism and wrote Hebrews commentaries which served as systematic rebuttals. William Gouge deployed typology and Ramism to rebind the two dispensations (chapter six), and John Owen revised received expressions of the covenant in order to permit more development within God’s plan while retaining unity of purpose before and after Jesus (chapter seven).